Lumpectomy Specimen Radiography: Does Orientation or 3-Dimensional Tomosynthesis Improve Margin Assessment?. Issue 3 (August 2019) - Mario, Julia; Venkataraman, Shambhavi; Fein-Zachary, Valerie; Knox, Mark; Brook, Alexander; Slanetz, Priscilla
Purpose: Our purpose was twofold. First, we sought to determine whether 2 orthogonal oriented views of excised breast cancer specimens could improve surgical margin assessment compared to a single unoriented view. Second, we sought to determine whether 3D tomosynthesis could improve surgical margin assessment compared to 2D mammography alone. Materials and Methods: Forty-one consecutive specimens were prospectively imaged using 4 protocols: single view unoriented 2D image acquired on a specimen unit (1VSU), 2 orthogonal oriented 2D images acquired on the specimen unit (2VSU), 2 orthogonal oriented 2D images acquired on a mammogram unit (2V2DMU), and 2 orthogonal oriented 3D images acquired on the mammogram unit (2V3DMU). Three breast imagers randomly assessed surgical margin of the 41 specimens with each protocol. Surgical margin per histopathology was considered the gold standard. Results: The average area under the curve (AUC) was 0.60 for 1VSU, 0.66 for 2VSU, 0.68 for 2V2DMU, and 0.60 for 2V3DMU. Comparing AUCs for 2VSU vs 1VSU by reader showed improved diagnostic accuracy using 2VSU; however, this difference was only statistically significant for reader 3 (0.73 vs 0.63, P = .0455). Comparing AUCs for 2V3DMU vs 2V2DMU by reader showed mixed results, with reader 1 demonstrating increased accuracy (0.72 vs 0.68, P = .5984), while readers 2 and 3 demonstrated decreased accuracy (0.50 vs 0.62, P = .1089 and 0.58 vs 0.75, P = .0269). Conclusions: 2VSU showed improved accuracy in surgical margin prediction compared to 1VSU, although this was not statistically significant for all readers. 3D tomosynthesis did not improve surgical margin assessment.